The continuing value of twin studies in the omics era - van Dongen, Jenny; Slagboom, P. Eline; Draisma, Harmen H. M.; Martin, Nicholas G.; Boomsma, Dorret I. (Nature reviews. Genetics, 2012)
Key Points Twins are valuable subjects for studies in which control over genetic background and early environmental influences is desired. Monozygotic twins are derived from a single zygote and are therefore matched for genetic background. Dizygotic twins are derived from two zygotes and share the same amount of genetic material as normal siblings. Both types of twins share prenatal and early environmental influences. Twin registries worldwide have established vast collections of longitudinal phenotypic data as well as biological material in twins, offering a valuable resource for studying the molecular biology of complex traits. The classical twin design compares the phenotypic similarity of monozygotic and dizygotic twins to estimate the importance of heritable and environmental influences on complex trait variation. Classical twin studies have provided estimates of heritability for numerous traits in the biomedical, psychiatric and behavioural domain. Multivariate twin studies address the causes of association among phenotypes. Associations can be among different phenotypes or across age and are explained by common genetic or environmental influences. We describe studies that applied the classical twin design to unravel the importance of genetic and environmental influences on variation in DNA methylation, gene expression, metabolomic and proteomic profiles in various tissues and on the composition of gut microbial communities. The comparison of molecular profiles of phenotypically discordant monozygotic twin pairs is a powerful method to identify molecular characteristics associated with complex traits, including point mutations and genomic structural variation, differentially expressed and differentially methylated genes and metabolic profiles. Examples of this approach are given for a range of disorders and traits. Twin studies have long been used for dissecting the relative contributions of genetics and other factors to various phenotypes. This Review discusses how these traditional studies are now being integrated with modern omics technologies to provide a wide range of biological insights. The classical twin study has been a powerful heuristic in biomedical, psychiatric and behavioural research for decades. Twin registries worldwide have collected biological material and longitudinal phenotypic data on tens of thousands of twins, providing a valuable resource for studying complex phenotypes and their underlying biology. In this Review, we consider the continuing value of twin studies in the current era of molecular genetic studies. We conclude that classical twin methods combined with novel technologies represent a powerful approach towards identifying and understanding the molecular pathways that underlie complex traits.